Triumphing Over Adversity: Navigating Climate Change, Covid-19, and Conflict for Sustainable Development in the Post-Globalization Era - Samekto, FX Adji; Purwanti, Ani; Natalis, Aga (Journal of Ecohumanism, 2024)
This research examines the role of addressing global humanitarian issues in achieving the Sustainable Development Goals (SDGs) established by States at the UN Sustainable Development Conference in 2012. The SDGs aim to tackle key challenges related to sustainable development, covering environmental, social, and economic dimensions. However, achieving a balance between environmental protection, economic growth, and social inclusion is a complex task requiring continuous efforts and commitment. Through a socio-legal approach, this study identifies three global humanitarian issues as obstacles to the SDGs: climate change, the ongoing COVID-19 pandemic, and conflicts between States, specifically the Russo-Ukrainian War. Addressing climate change is crucial as it poses significant threats to the environment and human life. The COVID-19 pandemic exacerbates existing challenges, impacting health systems, economies, and social well-being. State conflicts disrupt peace and stability, impeding progress towards development goals. Overcoming these obstacles necessitates international cooperation, policy reforms, and effective governance, prioritizing sustainability, resilience, and inclusiveness. By addressing these humanitarian issues, we can enhance the likelihood of achieving the SDGs and building a more sustainable and equitable future for all.